DEVELOPMENT OF STRUCTURED STUDENT WORKSHEETS ON PROBLEM-BASED LEARNING MATERIAL LINEAR EQUATIONS WITH ONE VARIABLE - Rismarini, Rani Yunita; Hariyani, Sri; Pranyata, Yuniar Ika Putri (Universitas Muhammadiyah Ponorogo, 2024)
This research was conducted because the effectiveness of using Student Worksheets (LKS) at the junior high school level is still inadequate. This research aims to develop structured worksheets for problem-based mathematics learning with material on linear equations in one variable that is valid, practical, and effective. This research refers to the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. This worksheet is designed to guide seventh-grade junior high school students in understanding the basic concepts of linear equations in one variable, identifying the elements in the equation, mastering techniques for solving linear equations, and applying these concepts in real-world situations. The structured worksheets developed were tested according to the level of validity, practicality, and effectiveness. LKS validation is carried out by material substance experts and teaching material design experts. The practicality assessment was obtained from the results of the student response questionnaire. Assessment of the effectiveness of structured worksheets is obtained from the results of problem-based test questions. Structured worksheets contain student orientation to problems, organized learning activities, individual and group investigations, presentation of work results, as well as analysis and evaluation of the problem-solving process. Material substance validation showed a score of 3.819, which is very valid, while design validation showed a score of 3.70, which is very valid. The practicality test shows a score of 3.53, which is very practical, while the effectiveness test shows an average score of 77, which is very effective. Thus, structured worksheets used as tools in problem-based learning methods help students maximize their abilities in problem-solving. This research is important to carry out to facilitate teachers in providing worksheets that suit students' needs. By integrating these worksheets into classroom learning activities, it is hoped that they can help students solve mathematical problems, improve thinking patterns, and support more effective mathematics learning.